Good Bye to Petrol (Global Journal of Management and Business Research, 2016)
Today we are facing a great problem with the nature is pollution The major reason for pollution is the rapid growth of industrialization and the increase of vehicles The Carbon let out from the industries and the petrol and diesel cars which cause damages in the ozone layer It will affect the human society in a vast level First step or Need of an hour is creating mass awareness of this prime CO 2 problem to 7 35 billion population of world It is necessary to take Corporate social responsibility to reduce the Carbon level emission from their industries and to find out an alternate way for preventing the pollutions To avoid this and build a better world of healthy and pollution free is via Green marketing its scientifically implemented by change the trend in the automobile industry by E-cars i e Electric cars
Keywords: global warming; electric car; green marketing